Using Flipbooks in English Lessons for Formative Assessment in a Junior High School - Fitriyatus Sa'adah; Lies Amin Lestari; Ahmad Munir (Institut Agama Islam Negeri Palopo, 2022)
Many studies use a developmental design for media such as flipbooks, but there is small research that focuses on the implementation of flipbooks for English lessons for formative assessment. This study aims to explain the procedure and the experience of using flipbooks for English lessons for formative assessment because it is fully integrated into the teaching and learning process. A teacher and 8_grade students taking an International Class Program (ICP) were observed and interviewed. This study shows that the implementation of using flipbooks for learning English for formative assessment can be implemented well in schools that have technological means to support them. Some students feel like it is fun and practical to use flipbooks but there are also some who even feel uncomfortable using flipbooks.